The impact of germline mutations on targeted therapy. Issue 2 (January 2014) - Smith, Simon A; French, Tim; Hollingsworth, Simon J
Abstract Targeted therapies provide clinical benefit and improved therapeutic index. They have a growing prominence in patient management and focus in drug development. Their development is fuelled by our deepening knowledge of complex disease phenotypes and the need for improvement in new therapeutic efficacy. Extrapolation of the biological discovery through to new therapy targeting the causal biological variants to drive clinical gain is challenging. Here, we review the impact of germline mutations on targeted therapies. Historically, germline changes have contributed most to our understanding of disease mechanisms, drug metabolism and exposure, the latter of which has enabled safer positioning of therapies, such as clopidogrel and irinotecan. Similarly, prescreening for germline variants can avoid potentially fatal hypersensitivity reactions with abacavir. However, germline mutations continue to emerge as a central player in targeting therapeutics; ivacaftor drives partial restoration of mucus secretion in cystic fibrosis patients harbouring specific mutations, and treatment with olaparib exploits germline mutations in BRCA genes to drive synthetic lethality as an anti‐cancer mechanism. Central is definition of the causal link, association or contribution to the biological variance – and that we believe it is drugable for therapeutic gain. The demand for better therapies to treat modern diseases provides the appetite for continued investigation of the biological variance associated with germline mutations, inevitably leading to increased impact on the development of targeted therapeutics. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.